3D characterization of thermo-hydro-geological fields and estimation of power potential from Puga geothermal reservoir, Ladakh, India. (February 2020) - Jha, Shibani K.; Puppala, Harish; Mohan Kumar, M.S.
Abstract: Puga geothermal reservoir in India shows promising thermal manifestation zones. However, no systematic study is done to develop the 3D characterization of thermo-hydro-geological fields for this reservoir. A new methodology is developed to characterize porosity, thermal conductivity, density, specific heat, radioactive heat capacity and permeability as 3D block heterogeneity till a depth of 4 km from resistivity maps. The temperature field and stored heat energy in a geothermal reservoir are dependent on these parameters. Based on the developed characterization, 3D coupled flow and heat transport processes are simulated to estimate the extractable temperature and power to be generated from doublet extraction scheme with various operational conditions. The study finds energy recovery factor of 8.16% and 37.83% and minimum electrical power potential of 1.2 MWe and 50.4 MWe with 12% conversion efficiency from the depths of 250 m and 1875 m respectively over 50 years from Puga field. Sensitivity for fluid injection/extraction rate and well spacing is studied. The results show promising power potential from 1.4 to 2 km of depth. The block heterogeneity characterization is more reliable than layered and homogeneous characterization. The outcomes would certainly acquire a significant role in decision-making strategies for Puga geothermal exploitation. Highlights: 3D characterization of thermo-hydro-geological fields of Puga geothermal reservoir. Identification of exploitation zones at different depths. Estimation of stored heat energy in reservoirs based on block heterogeneity. Extractable power and energy recovery factors from Puga geothermal reservoir.